The Significance of Vascular Pathogenesis in the Examination of Corticobasal Syndrome - Dunalska, Anna; Pikul, Julia; Schok, Katarzyna; Wiejak, Katarzyna Anna; Alster, Piotr (Frontiers in Aging Neuroscience, 2021)
Corticobasal syndrome (CBS) is a clinical entity, classified as an atypical parkinsonism, characterised by both motor and higher cortical dysfunctions. The clinical manifestation of CBS is associated with several pathologies, among which corticobasal degeneration (CBD) is the most common. The aim of our study was to elaborate on the possible vascular pathogenesis of CBS and consider types of vascular lesions in these cases. Several cases of vascular CBS are described in the literature. The majority of presented patients were affected by internal carotid artery stenosis and ischemic strokes; few cases were associated with vascular malformations or autoimmune diseases. Vascular CBS is preceded by an abrupt onset. The clinical manifestation does not significantly differ with non-vascular CBS. Patients with vascular CBS are usually elderly; often with coexistent hypertension, dyslipidemia and diabetes mellitus. Inferring from our observations, cerebral hypoperfusion can play a significant role in neuropathological changes in neurodegenerative diseases. To our knowledge our paper is the first comprehensive review of vascular CBS and we are positive that our observations show that further research concerning the vascular pathogenesis of tauopathic atypical parkinsonisms is required.